1982
DOI: 10.1007/bf00288675
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and transcriptional activity of mouse oocyte chromosomes

Abstract: Lampbrush chromosomes of growing amphibian oocytes carry thousands of lateral loops each of which consists of a chromatin fiber heavily encrusted with nascent ribonucleoprotein fibrils. These are believed to be responsible for the accumulation and maintenance of RNA transcripts found stored in the egg. In the case of mammalian oocytes, lampbrush chromosomes are most likely to occur during the major growth phase and also possibly during pachytene-early diplotene stages of meiosis. We have examined pachytene and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
1
3
1
Order By: Relevance
“…It has been shown that changes in chromatin configuration in oocytes correlate with a decline in transcriptional activity [2,7,12]. This is consistent with the basic processes that are already well known in other cell types and in which acetylation of nucleosome core histones is essential in both chromatin remodeling and transcription.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…It has been shown that changes in chromatin configuration in oocytes correlate with a decline in transcriptional activity [2,7,12]. This is consistent with the basic processes that are already well known in other cell types and in which acetylation of nucleosome core histones is essential in both chromatin remodeling and transcription.…”
Section: Introductionsupporting
confidence: 67%
“…During this period, chromatin in the germinal vesicle (GV) is not static: first, growing oocytes display very strong transcriptional activity [2][3][4][5][6][7]; second, chromatin configuration is greatly altered in the latter half of the growth period [2,[6][7][8][9]; and third, recent studies have proven the existence of growth-dependent regulation of gene imprinting [10]. In the second of these activities, chromatin configuration is categorized broadly into two kinds by the presence or absence of a condensed mass of chromatin around the nucleolus.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, at the same stage (vitellogenesis) amphibian lampbrush chromosomes no longer possess a proteinaceous axis as seen on spread preparations and on sections of germinal vesicles [16]. Diplotene chromosomes of growing oocytes of Perinereis seem to be more similar to those of oocytes from mammalian species in which chromosomal axes were reported [14,15,17,18]. However, the interpretation of the present results obtained by in situ examination of diplotene chromosomes of Perinereis raises some questions.…”
Section: Chromatin and Chromosomal Axes Of Bivalentscontrasting
confidence: 54%
“…In mammalian spread chromosomes it is accepted that silver reveals proteinaceous axes [12]. In diplotene chromosomes, this was demonstrated not only in male Downloaded by [JAMES COOK UNIVERSITY] at 10:31 17 March 2015 293 meiosis [13] but also in growing oocytes [14,15]. Therefore, it is possible that the silver deposits observed in situ in germinal vesicles of oocytes of Perinereis reveal sections of the proteinaceous axial core of diplotene chromosomes.…”
Section: Chromatin and Chromosomal Axes Of Bivalentsmentioning
confidence: 87%
“…Usually, however, nonnucleolar transcription units of a variety of cell types and species are characterized by relatively few transcript fibrils, with extended unoccupied chromatin regions, indicative of a low level of ongoing transcriptional activity (Figs. 6 a, 7 b, c; see also Miller and Bakken 1972;Kierszenbaum and Tres 1975;Laird and Choii 1976;Foe et al 1976;Amabis and Nair 1976;Oda et al 1977;Villard and Fakan 1978;McKnight et al 1979;Harper and Puvion-Dutilleul1979;Bakken 1979, 1980;Hughes et al 1979;Cotton et al 1980;Petrov et al 1980;Beyer et al 1980Beyer et al , 1981Scheer et al 1981;Greimers and Deltour 1981 ;Bachvarova et al 1982;Rattner et al 1982; Puvion-DutilleuI1983).…”
Section: Visualization Of Transcriptionally Active N Onnucleolar Genesmentioning
confidence: 99%